2012
DOI: 10.1063/1.3679558
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of individual NiFe/Pt multilayer nanowires measured in situ in a scanning electron microscope

Abstract: The electrical properties of individual NiFe/Pt multilayer nanowires have been measured in situ by nanomanipulators in a scanning electron microscope. The electrical measurement of ∼50 nm diameter individual NiFe/Pt multilayer nanowires with polycrystalline microstructure shows that the nanowires have a resistivity of ∼2.2 × 10−7 Ω m (corresponding to a conductivity of ∼4.5× 106 Ω−1 m−1) and average resistance of individual NiFe-Pt interfaces of ∼0.2 Ω. The maximum failure current density of an individual NiFe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In 1995 Masuda et al demonstrated the controlled fabrication of nanoporous anodic alumina (AAO) templates [1], enabling the subsequent fast and reliable growth of electrodeposited metallic nanowires. Variations of this approach have developed to allow growth of complex nanowires, including modulated composition [2,3] and defined shape [4]. Electrodeposited nanowires of ferromagnetic materials are of interest due to their promise for applications in such as high-frequency devices [5], high-density magnetic recording [6], sensors [7], biomedicine [8] and spintronic devices [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In 1995 Masuda et al demonstrated the controlled fabrication of nanoporous anodic alumina (AAO) templates [1], enabling the subsequent fast and reliable growth of electrodeposited metallic nanowires. Variations of this approach have developed to allow growth of complex nanowires, including modulated composition [2,3] and defined shape [4]. Electrodeposited nanowires of ferromagnetic materials are of interest due to their promise for applications in such as high-frequency devices [5], high-density magnetic recording [6], sensors [7], biomedicine [8] and spintronic devices [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This asset is most convenient at small scales, not only to bring the tools within operating range of the targeted samples, but also for the manipulation of any three-dimensional object. It is thus used for in situ electrical [3] or mechanical [4] characterisation, including mechanical characterisation of biological samples like cells [5]. In such experiments, the SEM can also be coupled with FIB (focused ion beam) [6] or STM (scanning tunneling microscope) [7] techniques.…”
Section: A Micro-robotic Manipulationmentioning
confidence: 99%
“…In this context, the core/shell MNs have been investigated within the framework of the Ising model, such as effective-field theory (EFT) with correlations [13][14][15][16][17][18], mean-field theory (MFT) [19][20][21], and Monte Carlo (MC) simulations [22,23]. On the other hand, segmented MNs consist of alternating structures of wire-wire, tube-tube, and wire-tube structures; due to structural advantages compared to their counterparts, single-component nanostructures have been widely reported in the literature [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%